UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA MELALUI MEDIA REALIA KELAS II SDN GALUDRA SUMEDANG - Ramli, Hanah; Arrahim, Arrahim; Budianti, Yudi (Universitas Bhinneka PGRI, 2025)
This research aims to determine whether the use of realia media in sequential subtraction material can improve elementary school students' understanding of mathematical concepts. A total of 22 second grade students at SDN Galudra Sumedang took part in this research during the 2024 school year. This research used the classroom action research method. There are two cycles, each cycle consisting of 3 meetings. In each cycle, four main activities are carried out, namely: planning, implementation, observation and reflection. This research also uses data collection techniques, namely: interviews, observation, tests and documentation. The results of this research in cycle I, understanding of mathematical concepts showed an average of 68.0 with a completeness level of 68%. After carrying out the second cycle evaluation, there was a relevant increase with an average score of 91.0 with a completion rate of 91%. Classical completion in research of at least 75% of students achieving a score 66 is declared successful. The results of this study show that the use of Realia Media can improve understanding of mathematical concepts in class 2 students at SDN Galudra, Sumedang.